Robotic world models—conceptualization, review, and engineering best practices - Sakagami, Ryo; Lay, Florian S.; Dömel, Andreas; Schuster, Martin J.; Albu-Schäffer, Alin; Stulp, Freek (Frontiers in Robotics and AI, 2023)
The term “world model” (WM) has surfaced several times in robotics, for instance, in the context of mobile manipulation, navigation and mapping, and deep reinforcement learning. Despite its frequent use, the term does not appear to have a concise definition that is consistently used across domains and research fields. In this review article, we bootstrap a terminology for WMs, describe important design dimensions found in robotic WMs, and use them to analyze the literature on WMs in robotics, which spans four decades. Throughout, we motivate the need for WMs by using principles from software engineering, including “Design for use,” “Do not repeat yourself,” and “Low coupling, high cohesion.” Concrete design guidelines are proposed for the future development and implementation of WMs. Finally, we highlight similarities and differences between the use of the term “world model” in robotic mobile manipulation and deep reinforcement learning.